2015
DOI: 10.3389/fonc.2015.00154
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Transformation of Murine Oviductal Epithelial Cells: A Model System to Investigate the Onset of Fallopian-Derived Tumors

Abstract: High-grade serous carcinoma (HGSC) is the most lethal ovarian cancer histotype. The fallopian tube secretory epithelial cells (FTSECs) are a proposed progenitor cell type. Genetically altered FTSECs form tumors in mice; however, a spontaneous HGSC model has not been described. Apart from a subpopulation of genetically predisposed women, most women develop ovarian cancer spontaneously, which is associated with aging and lifetime ovulations. A murine oviductal cell line (MOELOW) was developed and continuously pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…Serial passaging of the MOE cells harboring both alterations resulted in an increase in all functional characteristics. These data are consistent with a previous study performed in serially passaged fallopian tube cells that indicate that aging is sufficient to induce functional alterations(16). In contrast to the tumorigenic model of serially passaging MOE cells on a CD1 background, the current model with PAX2 knocked down and p53 mutated did not form tumors after serial passaging.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Serial passaging of the MOE cells harboring both alterations resulted in an increase in all functional characteristics. These data are consistent with a previous study performed in serially passaged fallopian tube cells that indicate that aging is sufficient to induce functional alterations(16). In contrast to the tumorigenic model of serially passaging MOE cells on a CD1 background, the current model with PAX2 knocked down and p53 mutated did not form tumors after serial passaging.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated that the fallopian tube is likely one of the sources of origin of HGSC(9, 11, 13, 16, 38). However, no models of SCOUTs or of fallopian tube cells lacking PAX2 have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations